Compensation of elastic die and press deformations during sheet metal forming by optimizing blank holder design. Issue 1 (November 2020) - Burkart, M; Essig, P; Liewald, M; Beck, M; Mueller, M
Abstract: Shortened product development processes of car body components made of sheet metal combined with the upcoming lack of experts and craftsmen's in that field do challenge car manufacturers fundamentally. Required tryout time phases and manufacturing costs of complete die sets for car body panels are significantly influenced by their proper function in production and therefore by their highly developed manufacturing process. Looking in more detail, elastic deformation of costed two components and forming press behaviour under load impacts the contact areas between the sheet metal and the load specific spotted areas of the tool. Especially in deep drawing such contact areas between matrice and blank holder are strongly influenced by the sheet metal properties and the part flange behaviour in terms of thickening and thinning during the process. Modern advanced forming simulation models indeed increase precision of sheet metal forming simulation remarkably. For example, new friction models and structural modelling of forming die and forming press components do improve simulation accuracy, while still using rigid tool components. Considering tool stiffness and press deformation in the die design by generating specific blank or geometries via stiffness optimisation, elastic deformations and pressure distribution presumably can be homogenised. In this respect, this paper presents a numerical approach for minimising elastic deformations in drawing operations and thus reducing trial time in the early engineering face. Here a stiffness optimised blank holder is designed based on topology optimisation, taking into account press deformation characteristics such as used drawing pins underneath the blank holder and the drawing cushion box integrated in the press bolster. Afterwards, the new designs compared to conventionally designed die based on structural simulations. The main finding of this contribution is that new approach presented on the one hand leads to improved tool stiffness and reduced tryout effort and more robust production conditions on the other hand.